The Sacred Widow’s Forest: Indigenous Values and Socio-Ecological Governance of Kaombo Ohusii in Takimpo Village - Harnia, Sitti; Sarmadan, Sarmadan (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study examines how indigenous communities in Takimpo Village, Buton Regency, sustain forest conservation through a local wisdom–based management system known as Kaombo Ohusii (Widow Forest). Using a qualitative ethnographic approach, the study explores how cultural values, indigenous institutions, and spiritual beliefs operate collectively as governance mechanisms in forest management. Data were collected through participatory observation, in-depth interviews with customary leaders and community members, and documentation of indigenous practices related to Kaombo management. The analysis followed the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal two main patterns. First, Kaombo Ohusii functions as an integrated socio-ecological governance system in which customary norms and moral authority regulate forest access without reliance on formal enforcement. Second, the system incorporates social protection by prioritizing access for widows and economically vulnerable women, demonstrating that ecological conservation and social equity are mutually reinforcing within indigenous governance structures. Spiritual beliefs associated with ancestral guardianship further strengthen community compliance and long-term forest stewardship. These findings contribute empirically to discussions on community-based conservation and environmental humanities. From a policy perspective, the study underscores the importance of recognizing and strengthening customary institutions in developing culturally responsive and socially inclusive forest conservation strategies in Indonesia.